2015
DOI: 10.1016/j.jarmac.2015.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking the past: Children's early memories and maternal reminiscing as a function of family structure.

Abstract: The present research explores the role of family structure and maternal reminiscing in childhood amnesia in middle childhood (age 7-11 years). Children from non-nuclear (solo parent, blended, extended; n = 13) or nuclear families (two biological parents; n = 13) were interviewed about their two earliest memories; they also reminisced with their mothers about shared past events. Children from non-nuclear families had earlier memories than children from nuclear families. Mothers from non-nuclear families generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(9 citation statements)
references
References 47 publications
2
7
0
Order By: Relevance
“…There is also some evidence that earlier childhood memories are reported by individuals for whom early parental separation was particularly painful (Artioli & Reese, 2014; Artioli, Reese, & Hayne, 2015). For example, Artioli and Reese (2014) assessed the earliest memories of young adult New Zealanders from families with separated parents; those for whom the separation occurred when the children were very young (<7 years of age) also had earlier memories than did those whose parents separated later.…”
mentioning
confidence: 99%
“…There is also some evidence that earlier childhood memories are reported by individuals for whom early parental separation was particularly painful (Artioli & Reese, 2014; Artioli, Reese, & Hayne, 2015). For example, Artioli and Reese (2014) assessed the earliest memories of young adult New Zealanders from families with separated parents; those for whom the separation occurred when the children were very young (<7 years of age) also had earlier memories than did those whose parents separated later.…”
mentioning
confidence: 99%
“…In terms of other structural variables, mothers with less than a high school diploma seem to be less elaborative during reminiscing than mothers with at least a high school diploma, but college experience does not seem to add additional prediction (Raikes & Thompson, 2008). One study found that mothers who are rearing children alone also seem to be less elaborative during reminiscing than mothers who are partnered (Artioli et al, 2015). Overall, whereas child characteristics related to maternal reminiscing style have been heavily researched, maternal characteristics simply have not, and much about maternal factors that predict or are related to reminiscing style remains to be discovered.…”
Section: Maternal Reminiscing Stylementioning
confidence: 99%
“…Mothers who have received more years of education appear to be more likely to adopt an elaborative style of reminiscing (Artioli et al, 2015; Reese & Newcombe, 2007). Existing research mostly comprises middle-class educated samples, so less is known about how elaboration style relates to SES and other demographic variables in more diverse samples (Wu & Jobson, 2019).…”
Section: Reminiscing Origins: Microsystem Factorsmentioning
confidence: 99%